2017
DOI: 10.3390/ijms18020386
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nerve Growth Factor (NGF) and Its Precursor Forms in Oral Wound Healing

Abstract: Nerve growth factor (NGF) and its different precursor forms are secreted into human saliva by salivary glands and are also produced by an array of cells in the tissues of the oral cavity. The major forms of NGF in human saliva are forms of pro-nerve growth factor (pro-NGF) and not mature NGF. The NGF receptors tropomyosin-related kinase A (TrkA) and p75 neurotrophin receptor (p75NTR) are widely expressed on cells in the soft tissues of the human oral cavity, including keratinocytes, endothelial cells, fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 48 publications
0
20
0
2
Order By: Relevance
“…Thus, from our findings, ANT-rich extract treatments may not result in direct repair during the initiation stage of the wound healing but promote a permeability of collagen to the lesion, epithelial cell proliferation and differentiation, and repair the destructive mucosa during the late stage. Nevertheless, specific growth factors such as nerve growth factor [ 36 ] or drugs such as corticosteroids [ 37 ] which take part in the effective wound healing in the oral cavity should be employed to compare the efficacy with ANT-rich extract.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, from our findings, ANT-rich extract treatments may not result in direct repair during the initiation stage of the wound healing but promote a permeability of collagen to the lesion, epithelial cell proliferation and differentiation, and repair the destructive mucosa during the late stage. Nevertheless, specific growth factors such as nerve growth factor [ 36 ] or drugs such as corticosteroids [ 37 ] which take part in the effective wound healing in the oral cavity should be employed to compare the efficacy with ANT-rich extract.…”
Section: Discussionmentioning
confidence: 99%
“…Mice have the same three major pairs of salivary glands, located in a similar location ( Figure 1B). Mice differ from humans in that the SMG has an additional ductal network that connects the intercalated ducts to the striated ducts and is the main source of growth stimulatory molecules such as nerve growth factor and epidermal growth factor (Gresik, Chung, Barka, & Schenkein, 1980;Schenck, Schreurs, Hayashi, & Helgeland, 2017).…”
mentioning
confidence: 99%
“…Only few to moderate number of NGF-containing nerve fibres, nerve fibre bundles and neuroendocrine cells were observed in our patients' palate and alveolar process mucosa. NGF has been found to play a role in processes which are important in orofacial development -cell survival, cellular proliferation, restitution, up-regulation of anti-apoptotic proteins and remodellation [22]. Therefore, it can be suggested that the detected number of NGF-containing neuronal structures in our patients' mucosa could possibly be not enough to provide for the previously mentioned processes and partially play a role in cleft development.…”
Section: Discussionmentioning
confidence: 79%
“…NGF plays an important role in survival, growth and maintenance of neurons in the mammalian nervous system, performing functions through two different receptors, TrkA and p75 [20,21]. NGF has been found to play a role in oral epithelial wound healing by participating in tissue remodelation, cellular proliferation, restitution, up-regulation of anti-apoptotic proteins and inflammation [22].…”
Section: Introductionmentioning
confidence: 99%